Polyglycolic acid‐collagen tube combined with collagen‐binding basic fibroblast growth factor accelerates gait recovery in a rat sciatic nerve critical‐size defect model. Issue 2 (23rd April 2019) - Fujimaki, Hisako; Uchida, Kentaro; Inoue, Gen; Matsushita, Osamu; Nemoto, Noriko; Miyagi, Masayuki; Inage, Kazuhide; Takano, Shotaro; Orita, Sumihisa; Ohtori, Seiji; Tanaka, Keisuke; Sekiguchi, Hiroyuki; et al.
Abstract: Several nerve conduits have been investigated for their potential as alternative sources of autografts for bridging neural gaps. However, autologous nerve transplants remain the most effective for nerve repair. We examined clinically approved nerve conduits containing collagen and polyglycolic acid (PGA‐c) combined with collagen‐binding basic fibroblast growth factor (bFGF) containing a polycystic kidney disease (PKD) domain and collagen binding domain (CBD) (bFGF‐PKD‐CBD) in a rat 15‐mm sciatic nerve critical‐size defect model. The treatment groups were: PGA‐c immersed in phosphate‐buffered saline (PBS) (PGA‐c/PBS group), bFGF (PGA‐c/bFGF group), or bFGF‐PKD‐CBD (PGA‐c/bFGF‐PKD‐CBD group), and no treatment (Defect group). Gait and histological analyses were performed. Four weeks after treatment, the recovery rate of the paw print area was significantly greater in the PGA‐c/bFGFPKD‐CBD group than the PGA‐c/PBS and PGA‐c/bFGF groups. Mean intensity of paw prints was significantly greater in the PGA‐c/bFGF‐PKD‐CBD group than the PGA‐c/PBS and Defect groups. Swing time was significantly greater in the PGA‐c/PBS, PGA‐c/bFGF, and PGA‐c/bFGF‐PKD‐CBD groups than the Defect group. At 8 weeks, all three parameters were significantly greater in the PGA‐c/PBS, PGA‐c/bFGF, and PGA‐c/bFGF‐PKD‐CBD groups than the Defect group. Regenerated myelinated fibers were observed in 7/8 (87.5%) rats in the PGA‐c/bFGF‐PKD‐CBD group after 8 weeks, and in 1/8 (12.5%) and 3/8 (37.5%) rats in the PGA‐c/PBS and PGA‐c/bFGF groups, respectively. PGA‐c/bFGF‐PKD‐CBD composites may be promising biomaterials for promoting functional recovery of long‐distance peripheral nerve defects in clinical practice.